2015
DOI: 10.1117/12.2187009
|View full text |Cite
|
Sign up to set email alerts
|

Proton irradiation of the CIS115 for the JUICE mission

Abstract: The CIS115 is one of the latest CMOS Imaging Sensors designed by e2v technologies, with 1504x2000 pixels on a 7 µm pitch. Each pixel in the array is a pinned photodiode with a 4T architecture, achieving an average dark current of 22 electrons pixel -1 s -1 at 21°C measured in a front-faced device. The sensor aims for high optical sensitivity by utilising e2v's back-thinning and processing capabilities, providing a sensitive silicon thickness approximately 9 µm to 12 µm thick with a tuned anti-reflective coatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…It also documents that the recovery of pre radiation dark current following a thermal anneal has a near identical relative effectiveness, highlighting the anneal characteristics are independent of the proton fluence. Moreover, furthering on from the work of [13], figure 2 shows that following a thermal anneal the mean value of dark current (in electrons) is decreased for each of the irradiated devices. Creating a fit between the mean dark current values at EOL proton fluence and the temperature of the device in kelvin using the exponential relationship from (3.1), similar to the ones presented in [15], dark current response of the CIS115 at a range of temperatures can be inferred.…”
Section: Dark Current Increase With Irradiationmentioning
confidence: 67%
See 2 more Smart Citations
“…It also documents that the recovery of pre radiation dark current following a thermal anneal has a near identical relative effectiveness, highlighting the anneal characteristics are independent of the proton fluence. Moreover, furthering on from the work of [13], figure 2 shows that following a thermal anneal the mean value of dark current (in electrons) is decreased for each of the irradiated devices. Creating a fit between the mean dark current values at EOL proton fluence and the temperature of the device in kelvin using the exponential relationship from (3.1), similar to the ones presented in [15], dark current response of the CIS115 at a range of temperatures can be inferred.…”
Section: Dark Current Increase With Irradiationmentioning
confidence: 67%
“…It also documents that the recovery of pre radiation dark current following a thermal anneal has a near identical relative effectiveness, highlighting the anneal characteristics are independent of the proton fluence. Moreover, furthering on from the work of [12], Figure 2 shows that following a thermal anneal the mean value of dark current is decreased for each of the irradiated devices.…”
Section: Dark Current Increase With Irradiationmentioning
confidence: 67%
See 1 more Smart Citation
“…In radiation studies of Teledyne-e2v CIS for other missions, such as the CIS115 for JANUS, 8 the BOL dark current and Total Ionising Dose (TID)-induced dark current has been insignificant compared to the increase in bright pixel defects induced by the TNID radiation environment. 9,10 The increased pitch and depleted volume in the CIS221-X (when compared to the partially depleted 7 µm pixel of the CIS115) will increase the dark current defect density per pixel, and therefore it is even more critical to understand the effect of TNID-induced dark current defects on the overall imager performance. The detailed analysis of the TNID-induced CIS115 bright pixel defect has been utilised to build a model for the THESEUS pixel and radiation environment.…”
Section: Dark Current and Device Operating Temperaturementioning
confidence: 99%
“…The CIS115 is undergoing radiation qualification to identify and quantify any changes in performance parameters that can be expected during the mission lifetime and confirm that it meets specifications for camera performance throughout the mission. A study on displacement damage in the CIS115 has been reported [5] showing good device performance following exposure to an EOL equivalent fluence of protons. An ionising radiation damage campaign has been undertaken which will be presented here.…”
Section: The Cis115 In the Janus Instrumentmentioning
confidence: 99%